Precision measurement of the W boson decay branching fractions in proton-proton collisions at √s=13 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Physical Review D)
The leptonic and inclusive hadronic decay branching fractions of the W boson are measured using proton-proton collision data collected at p s = 13 TeV by the CMS experiment at the CERN LHC, corresponding to an integrated luminosity of 35.9 fb???1. Events characterized by the production of one or two W bosons are selected and categorized based on the multiplicity and flavor of reconstructed leptons, the number of jets, and the number of jets identified as originating from the hadronization of b quarks. A binned maximum likelihood estimate of the W boson branching fractions is performed simultaneously in each event category. The measured branching fractions of the W boson decaying into electron, muon, and tau lepton final states are (10.83 ?? 0.10)%, (10.94 ?? 0.08)%, and (10.77 ?? 0.21)%, respectively, consistent with lepton flavor universality for the weak interaction. The average leptonic and inclusive hadronic decay branching fractions are estimated to be (10.89 ?? 0.08)% and (67.32 ?? 0.23)%, respectively. Based on the hadronic branching fraction, three standard model quantities are subsequently derived: the sum of squared elements in the first two rows of the Cabibbo???Kobayashi???Maskawa (CKM) matrix Pij IVijI2 = 1.984 ?? 0.021, the CKM element IVcsI = 0.967 ?? 0.011, and the strong coupling constant at the W boson mass scale, ??S(m2W) = 0.095 ?? 0.033.